2017
DOI: 10.1016/j.freeradbiomed.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation induces long-term senescence in endothelial cells through mitochondrial respiratory complex II dysfunction and superoxide generation

Abstract: Ionizing radiation causes oxidative stress, leading to acute and late cellular responses. We previously demonstrated that irradiation of non-proliferating endothelial cells, as observed in normal tissues, induces early apoptosis, which can be inhibited by pretreatment with Sphingosine-1-Phosphate. We now propose to better characterize the long-term radiation response of endothelial cells by studying the molecular pathways associated with senescence and its link with acute apoptosis. First, senescence was valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 43 publications
1
70
0
Order By: Relevance
“…Indeed, we did not observe increased rates of γН2АХ foci at passages 3 and 5 after irradiation, implying that irradiated MSCs (at least at the doses used here) do not transmit the residual γH2AX foci through the cell divisions, as described by Vaurijoux et al [ 71 ]. At the same time the observed high rates of γН2АХ foci in the progeny (passages 8 and 11) of 1000 mGy-exposed cells is consistent with radiation-induced genome instability [ 72 , 73 ] or accelerated cellular senescence [ 74 , 75 ]. Genome instability and senescence are not necessarily linked.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, we did not observe increased rates of γН2АХ foci at passages 3 and 5 after irradiation, implying that irradiated MSCs (at least at the doses used here) do not transmit the residual γH2AX foci through the cell divisions, as described by Vaurijoux et al [ 71 ]. At the same time the observed high rates of γН2АХ foci in the progeny (passages 8 and 11) of 1000 mGy-exposed cells is consistent with radiation-induced genome instability [ 72 , 73 ] or accelerated cellular senescence [ 74 , 75 ]. Genome instability and senescence are not necessarily linked.…”
Section: Discussionmentioning
confidence: 53%
“…In a separate study, quantitative mass spectrometry in mitochondria isolated from the brain of 5, 12 and 24 month old mice revealed changes in the expression of proteins involved in catabolic pathways and generation of metabolites, further highlighting that age-specific metabolic demands may influence the patterns of protein synthesis [ 25 ]. The induction of senescence (discussed more fully later) has also been linked to deterioration of mitochondrial OXPHOS [ 28 , 29 , 30 ].…”
Section: Regulation Of Mitochondrial Gene Expression and Age-relatmentioning
confidence: 99%
“…Experiments using ApoE −/− mice which harbor a polymerase gamma mutation (that makes them more prone to accumulate mtDNA mutations) revealed that elevated aortic mtDNA damage was associated with an increased atherosclerotic plaque size, thus providing direct causal evidence (Yu et al, 2013). Moreover, a range of studies have demonstrated the presence of changes in mitochondrial number, structure and function after exposure of different types of cells and tissues to high (5-20 Gy) doses of ionizing radiation, indicating induction of mitochondrial dysfunction (Pandey et al, 2006;Nugent et al, 2007;Dayal et al, 2009;Hu et al, 2017;Lafargue et al, 2017). However, findings specifically focusing on the effect of ionizing radiation exposure on endothelial mitochondria are scarce.…”
Section: Introductionmentioning
confidence: 99%